Towards green marine technology and transport : proceedings of the 16th International Congress of the International Maritime Association of the Mediterranean (IMAM 2015), Pula, Croatia, 21-24 September 2015 /: proceedings of the 16th International Congress of the International Maritime Association of the Mediterranean (IMAM 2015), Pula, Croatia, 21-24 September 2015. ([2015]) - International Maritime Association of the Mediterranean., International Congress, (16th) 2015 (Pula, Croatia)
No abstract available